Extremophilic Microbes and Metabolites Diversity, Bioprospecting and Biotechnological Applications - Najjari, Afef; Cherif, Ameur; Sghaier, Haïtham; Imene Ouzari, Hadda (IntechOpen, 2021)
This book focuses on the diversity and biotechnological applications of metabolites produced by extremophilic microbes thriving in different ecological niches citing the low troposphere, the gastrointestinal tract of ruminants, tropical dry forest, and saline ecosystems. These studies were based on metabolomics and molecular approaches like metagenomics and single-cell genomic analyses. Various implications of Electro-Rheological Fluid are also discussed. The editor embarked on this writing project entitled "Extremophilic Microbes and Metabolites - Diversity, Bioprospecting, and Biotechnological Applications" to make pertinent contributions accessible to the scientific community. Hopefully, a large audience will benefit from the chapters of this book.